Cross-National Competency Alignment Framework for Global Nursing Practice Integration - Akonasu Qudus Hungbo; Christiana Adeyemi; Opeoluwa Oluwanifemi Ajayi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Globalization and increased nurse mobility have heightened the demand for standardized competencies across national boundaries to ensure safe, effective, and equitable nursing care. However, variations in educational curricula, clinical standards, and regulatory frameworks often hinder seamless integration of nursing professionals into foreign healthcare systems. This study introduces a Cross-National Competency Alignment Framework (CNCAF) aimed at harmonizing nursing competencies to facilitate global nursing practice integration. The framework was developed through a systematic review of international nursing competency models, including those from the International Council of Nurses (ICN), American Nurses Association (ANA), and the European Federation of Nurses Associations (EFN). Key domains were identified and mapped against national standards from five countries with high nurse migration rates. Stakeholder consultations were conducted with 40 nursing educators, regulators, and practitioners across the United States, Canada, the United Kingdom, Nigeria, and the Philippines. The CNCAF comprises five core competency clusters: clinical proficiency, ethical and legal practice, cultural and linguistic adaptability, interprofessional collaboration, and technology-enabled care. Findings indicate that alignment gaps were most pronounced in digital health literacy and culturally sensitive communication. Participants emphasized the need for global competency benchmarking, mutual recognition agreements, and preparatory transition programs to support international nurse integration. Pilot testing of the CNCAF in two transnational nursing exchange programs demonstrated improved readiness, reduced onboarding time, and enhanced interprofessional communication among migrant nurses. The framework also provided a foundation for joint curriculum development and international accreditation discussions. This study concludes that the CNCAF offers a strategic tool for aligning diverse nursing standards, enhancing workforce flexibility, and addressing global health workforce shortages. Policymakers and nurse leaders are encouraged to adopt and refine the framework to support equitable mobility and professional growth in global nursing practice.